Turkey-Hen Amino Acid Composition of Brain and Eyes: Turkey-Hen Amino Acid - Adeyeye, Emmanuel Ilesanmi (Biological Sciences - PJSIR, 2015)
The amino acids composition of the brain and eyes of the mature Turkey-hen (Meleagris gallopavo L.), were determined on dry weight basis. Total essential amino acids ranged from 35.1-36.0 g/100 g as 49.5- 49.8% of the total amino acids. The amino acid score showed that lysine ranged from 0.76-0.91 (on whole hen?s egg comparison), 0.85-1.03 (on provisional essential amino acid scoring pattern), and 0.81-0.98 (on suggested requirement of the essential amino acid of a preschool child). The predicted protein efficiency ratio was 1.94-2.41, whilst essential amino acid index range was 1.06-1.08 and the calculated isoelectric point range was 3.97-4.18. The correlation coefficient (rxy) was positively high and significant at r = 0.01 for the total amino acids, amino acid scores (on the whole hen?s egg comparisons made) and the isoelectric point. On the whole, the eyes were better in 12/18 or 66.7% parameters of the amino acids than the brain of Turkey-Hen.